Treatment with Saccharomyces boulardii and Escherichia coli Nissle is safe and associated with reduced nosocomial transmission of vanB vancomycin-resistant Enterococcus faecium on an early rehabilitation ward in Germany: a retrospective analysis - Borgmann S; Rieß B; Siegmund R; Werner G; Klare I (Dove Medical Press, 2019)
Stefan Borgmann,1 Beate Rieß,1 Rabea Siegmund,1 Guido Werner,2 Ingo Klare2 1Department of Infectious Diseases and Infection Control, Ingolstadt Hospital, Ingolstadt, Germany; 2National Reference Centre for Staphylococci and Enterococci, Robert Koch Institute, Wernigerode Branch, Wernigerode, Germany Purpose: According to the WHO vancomycin-resistant Enterococcus faecium (VRE) belongs to the microorganisms for which new antibiotics are urgently needed. Depending on the type of vancomycin resistance vanA gene VRE is differentiated from vanB VRE and other types. In this retrospective analysis the results of VRE surveillance performed at a German tertiary hospital with approximately 1,200 beds between 2013 and 2017 are shown.Patients and methods: Rectal screening swabs were taken at admission and once per week on the early rehabilitation ward of Ingolstadt Hospital (ERWIN) but not at other wards. The number of VRE colonized patients was evaluated by using appropriate computer software (LabCentre, Hybase). The Hybase program was also used to find out the number of Saccharomyces boulardii and multi-susceptible Escherichia coli Nissle in blood cultures of patients at ERWIN. The mechanism of vancomycin resistance was examined by PCR and clonality of VRE strains was analyzed by pulsed-field gel electrophoresis.Results: Between 2013 and 2015 the number of VRE increased from 30 to 78 per year whereas in 2016 and 2017 the number declined to 51. Systematic analysis of the laboratory data revealed that this increase was driven by oligoclonal transmission of vanB VRE on ERWIN until August 2016 despite performing intensified infection control measures. However, afterward the number of VRE decreased at ERWIN and subsequently at the other wards. While searching for the reason behind this beneficial development we noticed that at ERWIN, patients treated with antibiotics received two probiotic medications simultaneously (S. boulardii, E. coli Nissle) for the duration of the antibiotic therapy plus an additional 2 days. There was no indication of side effects caused by these microorganisms, particularly no infections.Conclusion: Application of S. boulardii and E. coli Nissle was safe and associated with reduced transmission of VRE from patient to patient at ERWIN. Therefore, in our setting, probiotic treatment of patients receiving antibiotics contributed to the increase of patients’ safety. Keywords: microbiota, oligoclonal spread, outbreak, probiotics, vanB, bacterial spread, circuit model of bacterial transmission, vanA